Endogenous cannabinoid system: role in the development of endocrine disorders - Kadzharyan, V. G.; Solovyuk, A. O.; Bedzily, P. P. (Zaporozhye Medical Journal, 2013)
Historical background about medical application of cannabis was presented, and conception about endocannabinoid system and its role in endocrine pathology was described in review. Usage of pharmacological drugs that modulate activity of endocannabinoid system in accordance with evidence medicine positions were shown.